Implementation of Cashless Payments in Mitigating Fraud Payment Risks at W Bali Seminyak Hotel - Kusuma, I Gede Eka Jaya; Tuwi, I Wayan; Mareni, Ni Ketut (PT FORMOSA CENDEKIA GLOBAL, 2024)
The use of cashless payments in hotels is increasing as technology and consumer preferences change. This study explores the impact of implementing cashless payments in reducing the risk of payment fraud at W Bali Seminyak Hotel. Data on cashless payments over the past two years shows a significant increase in the use of cashless payments, while cash usage has decreased. This study aims to analyze the benefits of cashless payments in improving transaction security and the efficiency of hotel financial management. Through a qualitative approach, this study also explores changes in hotel financial policies and infrastructure as well as staff perceptions of cashless payments. The results are expected to provide valuable insights for the hospitality industry in managing the transition to more dominant cashless payments.